PEMBUATAN PETUNJUK TEKNIS ASPEK MEKANIS KARYA ILMIAH UNTUK MENINGKATKAN TARAF LITERASI MAHASISWA - Amirudin Amirudin; La Ode Sahidin; La Ode Syukur; La Ode Adili; Erny Harijaty (Jurnal Pengabdian NUSANTARA, 2022)
The purpose of this writing is to find out how to make technical guidelines for the mechanical aspects of scientific work to increase student literacy levels. There are two important aspects that must be considered, namely substantive aspects and mechanical aspects. The substantive aspect is related to the substance of the science being studied, while the mechanical aspect is the aspect that becomes the means of conveying the substantive aspect. This community service activity uses a focus group discussion (FGD) method or technique and is continued with socialization or training on how to write scientific papers based on technical guidelines for mechanical aspects which are elaborated into documents entitled Technical Guidelines for Mechanical Aspects of Writing Scientific Papers. The results of the dedication show that the writing mistakes that are often made by students in writing scientific papers are mechanical aspects which include spelling, punctuation, and grammar errors. In addition, there were also errors in the composition aspect caused by the lack of attention of students in reading the writing guide. With existing technical guidelines for scientific work, students are able to adjust their writing style according to thesis and journal writing standards so as to increase student literacy levels.